Shareholder voting in mergers and acquisitions: evidence from the UK - Tokbolat, Yerzhan (2019)
This thesis consists of three empirical chapters examining shareholder voting on mergers and acquisitions (M&A). The sample of 362 M&A deals approved by shareholders of UK publicly listed companies from 1997 to 2015 is used to advance our understanding of the shareholder voting process under the UK regulations, the determinants of voting dissent, the consequences of such voting on M&A performance, and the relationship between corporate diversification and shareholder voting.